Liberalizing Russian Gas Markets - An Economic Analysis - Finn Roar Aune; Rolf Golombek; Hilde Hallre; Arild Moe; Knut Einar Rosendahl (Center for Economic Studies and ifo Institute (CESifo), 2015)
The Russian gas market is highly regulated. In this paper we examine possible impacts of regulatory changes on the demand side of this market. In particular, we consider the effects on Russian energy consumers of removing natural gas subsidies, and how changes in Russian gas consumption may affect its gas export to Europe. We also examine the importance of Russian pipeline capacity to Europe, as well as impacts of hypothetical changes in Russian gas export behavior. For this purpose, we use a detailed numerical model for the energy markets in Europe and Russia – LIBEMOD. Our results suggest that removing implicit subsidies to Russian gas consumers will have substantial impacts on total consumption of gas in Russia, especially in the electricity sector. Gas exports to Europe will be significantly affected as more gas becomes available for exports. Removal of other market imperfections in the Russian energy markets has smaller impacts on prices and quantities than removing gas subsidies. More competitive Russian gas export behavior would lead to much higher gas export to Europe, but our results suggest that Russian welfare would drop due to lower gas export prices.
Keywords: Q41; Q48; F10; C63; 330; Russian gas prices; Russian gas export; European energy market